Journalists' appropriation of ICTs in news-gathering and processing: a case study of Grocott's Mail - Dugo, Habtamu Tesfaye (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2008)
This study set out to investigate Grocott's Mail journalists' appropriation of information and communication technologies in news-gathering and processing using the social shaping of technology as a theoretical lens. It mainly focuses on digital ICTs that journalists use in news-gathering and processing including the Internet, electronic mail, and mobile telephony. Grocott's Mail is a small-scale newspaper based in Grahamstown, South Africa. Using qualitative research method and the case study as its sub-method, the research reveals that Grocott's Mail journalists' appropriation of ICTs involves various opportunities and challenges in news-gathering and processing. In terms of the state of the existing technological infrastructure, the study reveals that since it embraced the digital ICTs in 2003, Grocott's Mail boasts an adequate ICT infrastructure for a small-scale African newspaper with 30 PCs and one laptop, and professional software for 28 permanent employees. On the other hand, the research reveals serious constraints with the existing ICTs: a huge need for staff training and capacity building to fully utilise the ICTs, and the need to look for ways of raising funds to either upgrade or replace the existing ICTs. Grocott's Mail journalists use the Internet to do background research on news stories, to verify the accuracy of information, and to check competition across other media. These are the merits of the Internet in news-gathering and processing. On the other hand, there are specific unintended consequences of the Internet such as wasting the company's working time, and its use leading to lazy/press release journalism. Informants unanimously indicate that the main problems of the Internet are heavy dependence on other online news-sources and wasting time on online entertainment. In terms of using email in news-gathering, the research finds email technology as having advantages such as being a tool of flexibility and speed, a tool for email interviews, and as a technology that promotes participatory journalism. On the other hand, challenges related to email include its limitations because of what interviewees view as its supplementary and small-scale use because of its low contextual richness as opposed to face to face interviews. In terms of cellular telephony, the study finds that regardless of the ubiquity of cell phones and cell phone networks, they have not yet been deployed in news-gathering and processing due to various constraints. These are cell phones not being a big factor in reporting, lack of a proper funding and refunding scheme, prevalence of negative attitudes towards cell phones, and lack of a business model. Thus, cellular phones seem to have little or no relevance in news-gathering and processing at Grocott's Mail presently.
Keywords: Grocott's Mail (Grahamstown, South Africa); Journalism -- South Africa -- Grahamstown; Journalists -- South Africa -- Grahamstown; Electronic news gathering -- South Africa -- Grahamstown; Journalism -- Data processing -- South Africa -- Grahamstown; Information technology -- South Africa -- Grahamstown; Reporters and reporting -- South Africa -- Grahamstown; Communication and technology -- South Africa -- Grahamstown